Antibiotic resistance peculiarities of S. aureus isolates, obtained from nasal and throat mucosa of outpatients, Chernivtsi city - Blinder, O. O.; Blinder, O. V.; Rotar, D. V.; Humenna, A. V. (Zaporozhye Medical Journal, 2019)
The purpose of this study was to determine the specificity of sensitivity to antibiotics of S. aureus strains isolated from nasal mucous membranes and tonsils, as well as to identify the factors of antibiotic resistance. Materials and methods. The pure culture method was used to study smears of the palatine tonsils, the nose and the secret of the external auditory canal of 561, 56 and 15 cultures, respectively. Identification of isolated cultures was carried out according to morphological, tinctorial, physiological and biochemical characteristics. The sensitivity of S. aureus strains to antibiotics was studied and analyzed, 211 of which were isolated from the mucous of the palatine tonsils and 18 - from the nasal mucous. All the isolated strains of S. aureus were determined for the presence of antibiotic resistance factors (FA) -ß-lactamases (BL) and penicillin-binding protein (PВPs). Results. High percentage of strains resistant to ß-lactam antibiotics and macrolides was found in both groups of studied cultures. However, the number of resistant forms to these antibiotics was higher among nasal strains. At the same time, none of the resistant strain to aminoglycosides, fluoroquinolones, lincosamides, tetracyclines, and vancomycin was detected among them. 9.57 % of the strains isolated from the tonsillar mucosa were resistant to the last one. BL and PВPs antibiotic resistance factors of isolated S. aureus strains were more frequent among nasal isolates (BL – 83.3 %, PВPs – 66.7 %) than in strains isolated from the palatine tonsils (BL – 66.3 %, PВPs – 38.6 %), P < 0.05. Sensitivity to antibiotics of S. aureus strains having both FA simultaneously (30 strains) and strains having none of them (26 strains) turned out to be different. Among the strains having both FA, 100 % were resistant to penicillin, 93.3 % to oxacillin, and 36.7 % to vancomycin. Whereas there were 3.9 %, 0.0 %, and 7.7 % strains without FA resistant to these antibiotics, respectively. Resistance to azithromycin was greater in the group of strains with FA: 26.7 % versus 7.7 % in the group without FA. The strains of both groups were highly sensitive with an insignificant difference to other studied antibiotics (aminoglycosides, fluoroquinolones, macrolides, lincosamides and tetracyclines). Conclusions. S. aureus strains isolated from the mucous membranes of the nose and tonsils differ in sensitivity to antibiotics and the presence of FA. The nasal strains of S. aureus are more likely to be resistant to ß-lactam antibiotics and macrolides. Vancomycin resistant strains of S. aureus are significantly more common among strains with FA.